ANALISA PERBANDINGAN UPAH BERDASARKAN PRODUKTIVITAS PEKERJA, UNTUK PEKERJAAN BESI STRUKTUR BETON BERTULANG - Anna Rumintang Nauli; Fithri Estikhamah (KERN, 2019)
ABSTRACT The cost for the work of a building and other structures, known as the cost of construction, is the important factor that needs to be known by every person working in the construction world. Wage workers hold very important role in determining the contractor for the price of a construction project. Wage costs are very related to the productivity of workers. Productivity of labor is influenced by several factors, both related to the labor itself and with the environment and government policy, which is referred to social security, salaries / wages, education, discipline, attitude, work ethics, nutrition, health, technology, production facilities , monetary, price distribution, investment licensing, business climate, employment, and so forth. From the results of the analysis of the obtained value of the average productivity of 29.96 m3 / day. Data characteristics of the workers and the productivity of the current calculation is done using the statistical SPSS with Chi-Square method to find out there is no relationship between the two variables are. In fact the two variables are related, where the variable characteristics that affect the variables age and experience. And to obtain a high productivity of labor is expected to have any age between age 25 - 32 years, have experience of 10 - 13 Year. For home workers the education variable does not affect the level of productivity. Wage workers will get a decent view of the productivity difference between the highest value of + 0.08% wage gain of Rp. 28,600 day while for the lowest value of -0.78% productivity gain wage Rp. 28,300 day.